Magnetism in pristine and chemically reduced graphene oxide - Diamantopoulou, A.; Glenis, S.; Zolnierkiwicz, G.; Guskos, N.; V. Likodimos (Journal of Applied Physics, 2017)
The evolution of magnetism for graphene oxide (GO) before and after chemical reduction was investigated by means of static magnetization and electron spin resonance (ESR) spectroscopy. Strong paramagnetism with a saturation magnetization of ∼1.2 emu/g and weak antiferromagnetic interactions were identified in pristine GO. Apart from spin-half defect centers, ESR spectroscopy indicated the excitation of high spin states, consistently with the high spin (S = 2) magnetic moments derived from the magnetization analysis, corroborating the formation of spatially "isolated" magnetic clusters in GO. A marked reduction of GO's magnetization (∼0.17 emu/g) along with an appreciable rise of diamagnetism (-2.4 × 10-6emu/g Oe) was detected after chemical reduction by sodium borohydride, reflecting the drastic removal of paramagnetic defects and the concomitant growth of sp2 domains in reduced graphene oxide (rGO). ESR revealed a large drop of the spin susceptibility for rGO, which, in addition to the main paramagnetic Curie component, showed an appreciable Pauli contribution. The latter together with the g-factor shift and the broadening of the ESR line indicated the coupling of localized spins with conduction electrons. The rGO ESR signal presented a metallic line shape, which could be analyzed in terms of two separate spectral components, a broad one that may be related to defect states strongly coupled with itinerant spins within the sp2 clusters and a narrow one due to edge/vacancy defect spins, indicative of rGO's persistent structural inhomogeneity. © 2017 Author(s).